A sustainable artwork from fabric waste: Jalinan memori / Sharifah Maryam Syed Azman - Syed Azman, Sharifah Maryam (UiTM Perak Press, 2021)
The Malaysian textile industry was the fifteenth largest producer and ninth largest in Asian Region. To overcome this issue, the practice of textile waste recycling is common in many countries. Sustainability practice can also be implemented through arts and craft. By utilizing textile waste, such as fabric scraps or leftover, artworks are also one of the mediums which can promotes sustainability. Jalinan Memori is one of the sustainable artworks which promotes upcycling technique by using fabric waste. This artwork adopted exploration method on weaving techniques which is called Kelarai Tulang Belut Berhati. Some of the elements of art which is visualised in this artwork are colours, form, shape and texture. Fabric scraps from chiffon materials, satin, and ribbons were used in this artwork. Four colours of purple, dark blue, white and yellow were chosen as these colours inspired from the UiTM logo. Jalinan Memori is an artwork which represented personal experience of the artist. With the current issues of sustainability, especially regarding fabric waste, this is one of the methods to show support in reducing the environmental impact. As educators, this is a responsibility way to reflect in art and design community.